A novel NiMn2O4@NiMn2S4 core-shell nanoflower@nanosheet as a high-performance electrode material for battery-type capacitors. (20th May 2022) - Lv, Xinrong; Min, Xiaoqin; Feng, Li; Lin, Xiaoyun; Ni, Yongnian
Abstract: This study reported a novel NiMn2 O4 @NiMn2 S4 core-shell nanoflower@nanosheet synthesized via a simple two-step hydrothermal method as an excellent electrode material for battery-type capacitors. The NiMn2 O4 @NiMn2 S4 was characterized by XRD, XPS, SEM and EDS. The "core" (NiMn2 O4 ) and "shell" (NiMn2 S4 ) are both active materials, and they both participate in the Faraday redox reaction to facilitate the NiMn2 O4 @NiMn2 S4 electrode to obtain more excellent electrochemical characteristics. The specific capacity for the NiMn2 O4 @NiMn2 S4 electrode reaches 803.08 C g −1 when the current density is 1 A g −1 . Moreover, the specific capacity retention rate of the NiMn2 O4 @NiMn2 S4 electrode reaches 91.5% after 5000 charge - discharge cycles when the current density is 20 A g −1 . The energy density for the NiMn2 O4 @NiMn2 S4 //AC device reaches 73.65 Wh kg −1 at a power density of 775.04 W kg −1 . Additionally, the NiMn2 O4 @NiMn2 S4 //AC demonstrates excellent self-discharge characteristics. Therefore, the NiMn2 O4 @NiMn2 S4 electrode material presents extensive application prospects for battery-type capacitors. Graphical abstract: Image, graphical abstract